Lidar Data Reduction for Unmanned Systems Navigation in Urban Canyon - Alfred Mayalu; Kevin Kochersberger; Barry Jenkins; François Malassenet (Remote Sensing, 2020)
This paper introduces a novel protocol for managing low altitude 3D aeronautical chart data to address the unique navigational challenges and collision risks associated with populated urban environments. Based on the Open Geospatial Consortium (OGC) 3D Tiles standard for geospatial data delivery, the proposed extension, called 3D Tiles Nav., uses a navigation-centric packet structure which automatically decomposes the navigable regions of space into hyperlocal navigation cells and encodes environmental surfaces that are potentially visible from each cell. The developed method is sensor agnostic and provides the ability to quickly and conservatively encode visibility directly from a region by enabling an expanded approach to viewshed analysis. In this approach, the navigation cells themselves are used to represent the intrinsic positional uncertainty often needed for navigation. Furthermore, we present in detail this new data format and its unique features as well as a candidate framework illustrating how an Unmanned Traffic Management (UTM) system could support trajectory-based operations and performance-based navigation in the urban canyon. Our results, experiments, and simulations conclude that this data reorganization enables 3D map streaming using less bandwidth and efficient 3D map-matching systems with limited on-board compute, storage, and sensor resources.